Effect of Nonelastic Compression With an Adjustable Wrap After Total Knee Arthroplasty. (November 2020) - Hendrickx, Ad A.; Krijnen, Wim P.; Bimmel, Richard; van der Schans, Cees P.; Damstra, Robert J.
Abstract : Swelling is a common phenomenon after total knee arthroplasty, with potential for negative impact on the rehabilitation process and final outcome. The aim of this study was to investigate the effectiveness of a new compression protocol with a self-adjustable, nonelastic compression wrap for the knee region. This study was conducted as a prospective comparative study. Total leg volume and the circumference of the knee at three levels were compared between groups. The results of our study suggest that the application of the new compression protocol has no effect on swelling in the acute postoperative phase (0–2 days) but reduces swelling at Day 14 within the subacute phase. The observed positive effect of the compression protocol could be of clinical importance in the subacute phase as well as for a subgroup of patients suffering from aberrant quadriceps weakness concomitant with knee swelling. Abstract : Supplemental Digital Content is Available in the Text.